Balcony Greenhouse – An EPS@ISEP 2017 Project - Calderon, Alisson (2018)
This paper presents the development process of a sustainable solution to grow aromatic plants in small houses. The solution is called The GreenHouse and is meant for people who live in small houses or city apartments and want fresh home grown aromatic plants, but have neither the time nor the space to grow them. The solution is intended to be sustainable and appropriate for people concerned with eating healthy, fresh food. The project was developed by a team of five students enrolled in the European Project Semester (EPS) at the Instituto Superior de Engenharia do Porto (ISEP) during the spring of 2017. EPS@ISEP is a project-based learning framework which aims to foster personal, teamwork and multidisciplinary problem-solving skills in engineering, business and product design students. Research and discussions within the team were done to develop the product. The existing solutions for growing fresh food in industrial and domestic applications as well as marketing, sustainability and ethical topics were researched and discussed. This way it was possible to define the requirements of The GreenHouse. The GreenHouse is semi-automatic and requires little interaction from the customer. It has two covers, a winter cover and a summer cover, to be changed depending on the season and weather. Solar energy and rainwater are used to enable the growth of aromatic plants, making this a sustainable system. The support is adaptable and made to fit different support sizes so it can be hanged on balconies or windows.